2022
DOI: 10.1021/acsbiomaterials.2c00256
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Construction of Black Titanium Oxide with a Multilevel Structure on a Titanium Alloy for Photothermal Antibacterial Therapy

Abstract: Postsurgical infection of orthopedic fixation materials is considered to be the main cause of fixation failure. To address the problem, clinical treatment often relies on long-term antibiotics, secondary surgery, and so forth, which cause pain and suffering to patients. Constructing a light-responsive surface structure on the implant has attracted widespread attention for the management of postsurgical infections because of its noninvasiveness and controllability. Nevertheless, the application of light-respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Further, amorphous black TiO 2 can also be synthesized and used for photocatalysis [ 201 ], which is important for applications such as for bone implants. Black TiO 2 was shown to exhibit biocompatibility [ 213 ], regenerative properties [ 214 ], photothermal properties [ 213 , 214 , 215 ], and microbicidal action [ 213 , 215 , 216 , 217 ], among others. As such, black TiO 2 shows promise for cancer treatment [ 214 , 215 ], as a bone implant coating, and for disinfection purposes [ 213 , 215 , 216 , 217 ].…”
Section: Tio 2 Photocatalysismentioning
confidence: 99%
See 2 more Smart Citations
“…Further, amorphous black TiO 2 can also be synthesized and used for photocatalysis [ 201 ], which is important for applications such as for bone implants. Black TiO 2 was shown to exhibit biocompatibility [ 213 ], regenerative properties [ 214 ], photothermal properties [ 213 , 214 , 215 ], and microbicidal action [ 213 , 215 , 216 , 217 ], among others. As such, black TiO 2 shows promise for cancer treatment [ 214 , 215 ], as a bone implant coating, and for disinfection purposes [ 213 , 215 , 216 , 217 ].…”
Section: Tio 2 Photocatalysismentioning
confidence: 99%
“…Black TiO 2 was shown to exhibit biocompatibility [ 213 ], regenerative properties [ 214 ], photothermal properties [ 213 , 214 , 215 ], and microbicidal action [ 213 , 215 , 216 , 217 ], among others. As such, black TiO 2 shows promise for cancer treatment [ 214 , 215 ], as a bone implant coating, and for disinfection purposes [ 213 , 215 , 216 , 217 ]. Similar to TiO 2 , the photo(electro)catalytic disinfection with black TiO 2 nanomaterials is also claimed to occur due to ROS, in particular, superoxide and/or hydroxyl radicals [ 216 , 217 ].…”
Section: Tio 2 Photocatalysismentioning
confidence: 99%
See 1 more Smart Citation
“…A large body of literature indicates that bacterial infection is one of the main causes of the clinical failure of titanium and titanium alloys as orthopedic implants. , Once bacterial adhesion occurs on the implant surface, bacterial colonies and biofilms will gradually form and disrupt the function of the implant. , Previous studies have shown that the early 4–6 h of bacterial adhesion is essential for long-term resistance to bacterial-associated infections and is particularly important. , …”
Section: Resultsmentioning
confidence: 99%
“…In the same milieu, Yang and co‐workers developed photoresponsive biomedical grade titanium alloy (Ti 6 Al 4 V) substrates with cauliflower‐like black titanium oxide layer with multilevel structures and lattice defects (contributed by oxygen vacancies and amorphous lattice) for orthopedic applications using pulsed laser ablation treatment. [ 129 ] Such structural aspects and defects allowed for better NIR absorption and promoted the photothermal abilities of the engineered substrates. Besides, these substrates were able to impart efficient bactericidal effects on S. aureus (99.37%) and E. coli (99.29%) via NIR‐induced photothermal effects.…”
Section: Impact Of Defect‐rich Structures On Improving the Biomedical...mentioning
confidence: 99%